GW24-e2176 Tongxinluo dose-dependently decreases apoptosis of mesenchymal stem cells under hypoxia and serum deprivation via the MEK/ERK1/2 pathway. (1st October 2013) - Na, Li; Zhang, Qian; Jin, Chen; Qian, Hai-Yan; Dong, Qiu-Ting; Xu, Hui; Zhang, Hao; Yang, Yue-Jin
Abstract : Objectives: Mesenchymal stem cells (MSCs) are one of the optimal candidates for myocardial infarction. However, the survival ratio of implanted cells in the infarcted heart is low. Tongxinluo (TXL) is a traditional Chinese herbal medicine with multiple cardiovascular protective effects and has been widely used in China to treat patients with coronary heart disease. MEK/ERK pathway plays an important role in mediating cell survival. Therefore, we hypothesised that TXL could promote MSCs survival under hypoxia and serum deprivation (H/SD) via MEK/ERK pathway. Methods: MSCs from the Sprague-Dawley rats bone marrow (60-80g, male) were pretreated with TXL (100-800 μg/ml) for 6 hours under H/SD. For inhibitor studies, the cells were preincubated with MEK1/2 inhibitor U0126 (10μM) for 1 hour prior to the addition of TXL (800 μg/ml). Cell apoptosis was assessed using Annexin V/propidine iodine (PI) by flow cytometry, apoptosis related protein bax, cytochrome C and bcl-2 was assessed by western blot. The expression of ERK1/2 and phosphorylation of ERK1/2 were measured by western blot. Results: We found that cell apoptosis was significantly upregulated under H/SD conditions compared with the normal. TXL decreases the apoptosis level in a dose-dependent manner especially in the 800mg/ml concentration, demonstrated by reduced apoptosis rate, decreased expression of pro-apoptotic protein bax and cytochrome C and incerased expression of anti-apoptotic protein bcl-2. Further, TXL upregulated the phosphorylation of ERK1/2. And treatment with U0126 attenuated the protective role of TXL coupled with downregulated phosphorylation of ERK1/2. Conclusions: TXL protects MSCs from H/SD injury via MEK/ERK1/2 pathway. It provides a further explanation for the protective effects of TXL on MSCs survival.